The Morphosyntactic Views of Abu Ali al-Farisi and Their Role in Guiding Quranic Readings in al-Razi’s al-Tafsir al-Kabir - Al-Atwi, Aisha Saeed Saleh (Arts for Linguistic & Literary Studies, 2024)
This study investigates the influence of Abu Ali al-Farisi’s morphosyntactic and linguistic perspectives as presented in al-Razi’s al-Tafsir al-Kabir. It analyzes al-Farisi’s views and their role in shaping Quranic readings, aiming to promote interdisciplinary connections among Quranic recitation, grammar, philology, exegesis, and jurisprudence. The research is organized into an introduction, a preface, two main sections, and a conclusion. The preface outlines key definitions and concepts. Section One explores al-Farisi’s key morphosyntactic views in al-Tafsir al-Kabir, while Section Two examines his notable linguistic opinions. A key finding reveals that al-Razi frequently aligns with al-Farisi’s perspectives in guiding Quranic readings but is not reluctant to diverge when evidence supports alternative interpretations. The study provides numerous examples to highlight such instances.